Analisis Kinerja Keuangan pada PT Sekar Bumi Tbk dengan Pendekatan Rasio Likuiditas, Solvabilitas dan Profitabilitas - Tarigan, Imelda Malona (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to evaluate financial performance as a tool for assessing the health and sustainability of a company, particularly in the face of intense business competition. Data were obtained from the financial statements of PT Sekar Bumi Tbk for the period 2020–2024. This article uses a quantitative descriptive method. A financial performance analysis was conducted using a ratio approach. The results of the analysis show that the current ratio is in the range of 1.31x to 1.57x during 2020–2024, below the industry standard of 2x. The quick ratio was recorded at an average of 0.81x, and the highest cash ratio only reached 42% in 2023, still below the ideal limit of 50%. The debt-to-asset ratio reached 50%, and the highest debt-to-equity ratio was 98% in 2021, exceeding the industry thresholds of 35% and 90%, respectively. Profitability performance also showed a downward trend, with the highest NPM of only 2.8%, ROA of 4.2%, and ROE of 8% in 2022, all three far below the industry standard. In conclusion, PT Sekar Bumi Tbk needs to improve the efficiency of liquidity management and profitability to maintain financial resilience and competitiveness amidst industry pressures.